Юзеф Пачоский. Херсонская флора. Том ІІ. Познань, 2008. - Мойсієнко, І.І.; Бойко, М.Ф.; Підгайний, М.М.; Ходосовцев, О.Є. (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
Юзеф Пачоский. Херсонская флора. Том ІІ. Познань, 2008.